How should we treat vascular and fibrotic lung disease in scleroderma? - Kravitz, Jared N (Medicine Reports Ltd, 2009)
Recent randomized trials suggest that evidence-based algorithms for systemic sclerosis can be developed to identify patients at risk for lung disease, follow lung disease progression, and modify disease with therapies of proven benefit. Recognition of disease subsets allows physicians to integrate physiology, overlapping disease manifestations, and predictable drug effects into a comprehensive disease management program.